Fenomena Tren Jual-Beli Online melalui Aplikasi Shopee di Starbucks Galuh Mas Karawang: Studi Fenomenologi mengenai Partner Starbucks Galuh Mas Karawang yang menggunakan Aplikasi Shopee - Fithriyah, Rifa; Abidin, Zainal; Mayasari, Mayasari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Shopee is an online marketplace that is in great demand by the people of Indonesia so that it becomes the leading market by ranking first in Indonesian e-commerce. Shopee itself is an online marketplace created by the SEA Group, which is an internet company based in Singapore. Shopee can stabilize its position in the first tier of the Indonesian marketplace market. This study aims to find out the motives, meanings, and experiences of Starbucks Partners Galuh Mas Karawang in using the Shopee application as an online buying and selling site. In this study, the authors used a qualitative method with the phenomenological approach of Alfred Schutz. The phenomenological approach aims to understand the meaning of an event and its influence on actors, the nature of this research is descriptive which means the preparation of research in a systematic, factual, and accurate manner. Methods of data collection using in-depth interviews, observation, and literature study. The criteria from the informants in this study were male or female Starbucks Partners who use the Shopee application as a means to sell or buy products. Informants who will be used as sources in this study amounted to 5 people.